Enzymatic Late‐Stage Oxidation of Lead Compounds with Solubilizing Biomimetic Docking/Protecting groups. Issue 68 (19th November 2018) - Vickers, Clare; Backfisch, Gisela; Oellien, Frank; Piel, Isabel; Lange, Udo E. W.
Abstract: Late‐stage functionalization of lead compounds is of high interest in drug discovery since it offers an easy access to metabolites and derivatives of a lead compound without the need to redesign an often long multistep synthesis. Owing to their high degree of chemoselectivity, biocatalytic transformations, enzymatic oxidations in particular, are potentially very powerful because they could allow the synthesis of less lipophilic derivatives of a lead compound. In the majority of cases, enzymatic oxidations have been used in an empirical way as their regioselectivity is difficult to predict. In this publication, the concept of using docking/protecting groups in a biomimetic fashion was investigated, which could help steer the regioselectivity of a P450BM3 ‐mediated oxidation. A novel set of docking/protecting groups was designed that can be cleaved under very mild conditions and address the often problematic aqueous solubility of the substrates. Vabicaserin was used as tool compound containing typical groups such as basic, aliphatic, and aromatic moieties. The results were rationalized with the help of in silico docking and molecular dynamic studies. Abstract : Novel solubilizing docking‐protecting groups enable the regioselective P450BM3 ‐mutant mediated late‐stage oxidation of lead compounds by binding the substrate (orange) in a biomimetic fashion (e.g., palmitic acid, green). Enzymatic oxidation, mild deprotection and purification yields hydroxylated derivatives that are difficult to obtain by classical chemical synthesis.